Analysis of Hermes’ Marketing Strategy: Evolution, brand positioning, and global impact - Zong Ziyi (SHS Web of Conferences)
This article provides an in-depth analysis of the marketing strategy of the Hermes brand. It begins by outlining the evolution of Hermes as a prominent luxury brand and examines its distinctive brand positioning and market impact. The study focuses on Hermes’s effective marketing strategies in the global market, encompassing its positioning in high-end luxury goods, differentiation strategies, distribution mechanisms, and publicity tactics. The research employs a literature review method and case analysis approach to scrutinize Hermes’s market positioning and consumer strategies. It reveals that Hermes has established a unique position in the luxury market by leveraging high-quality products, thereby effectively attracting and maintaining the loyalty of affluent consumers. Hermes’ marketing strategy mainly focuses on maintaining the luxury image and uniqueness of the brand, and maintaining market demand through limited distribution and high-priced strategies. In terms of digital marketing, Hermes has adopted a refined strategy, including using social media to display brand stories and products, creating targeted content, and interacting with consumers through online platforms, while maintaining the high-end image of the brand.